Gestión de tesorería en el Hospital Apoyo Iquitos, periodo 2022 - Soria Navas, Miguel Angel (2024)
The objective of this research was to determine Evaluate how treasury management was carried out at the Apoyo Iquitos Hospital, period 2022, with a type of quantitative research of non-experimental design and type of cross sectional design, the research instruments used were the questionnaire and the analysis of documents, with a population and sample of 30 workers between the Economy Unit, the Logistics, Planning and HR Unit of the Apoyo Iquitos Hospital, during the period 2022 and the records of the Hospital's deposit files; It was concluded that the survey reveals a high awareness and appreciation of regulatory compliance in treasury management, supported by 100% of those surveyed. It also points out areas of opportunity, such as the need to improve constant updating on regulations (58% constantly update), increase timely training on treasury regulations (only 16% receive it), and improve internal communication, with respect to control prior to the payment files, it was identified that, although 75% of the files were considered valid, the identification of the 25% that required observations highlights the opportunity to improve the quality and conformity of the documentation from the beginning, with Regarding the deposit periods of revenue collection reveals considerable variability, with figures fluctuating between 0 and 31 deposits in a month, a distribution of revenue by deposit period indicates that the majority of deposits (465) take more than 72 hours to process.